PERUBAHAN PERILAKU PENGGUNAAN OBAT PADA GURU DAN SISWA SEKOLAH MENENGAH ATAS ISLAM AL AZHAR 14 SEMARANG - Farroh Bintang Sabiti; Rina Wijayanti; Abdur Rosyid (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2021)
Community Service Activities are motivated by the knowledge and behavior of the community regarding drugs are still very limited, drugs are materials that are easily found around us. Improper use of drugs, without accurate and adequate information can lead to new diseases. The information contained on drug packaging is often not considered and understood properly by the public, besides that people do not understand how to store and dispose of drugs properly. This activity aims to increase public understanding and awareness about the importance of correct drug use behavior. This method is an educational activity with one-way counseling with community service team resource persons. Participants in community service activities involve homeroom teachers, UKS management teachers. UKS management teacher who will practice for students of Islamic Senior High School Al Azhar 14 Semarang. Providing counseling on this activity can change the behavior of drug use by teachers and students in an increasing manner so that participants are expected to be able to use the information for their families, other teachers, other students and the surrounding community.